G-protein-coupled receptor genes as protooncogenes: constitutively activating mutation of the alpha 1B-adrenergic receptor enhances mitogenesis and tumorigenicity. - Allen, L F (1991)
The alpha 1B-adrenergic receptor (alpha 1B-ADR) is a member of the G-protein-coupled family of transmembrane receptors. When transfected into Rat-1 and NIH 3T3 fibroblasts, this receptor induces focus formation in an agonist-dependent manner. Focus-derived, transformed fibroblasts exhibit high levels of functional alpha 1B-ADR expression, demonstrate a catecholamine-induced enhancement in the rate of cellular proliferation, and are tumorigenic when injected into nude mice. Induction of neoplastic transformation by the alpha 1B-ADR, therefore, identifies this normal cellular gene as a protooncogene. Mutational alteration of this receptor can lead to activation of this protooncogene, resulting in an enhanced ability of agonist to induce focus formation with a decreased latency and quantitative increase in transformed foci. In contrast to cells expressing the wild-type alpha 1B-ADR, focus formation in "oncomutant"-expressing cell lines appears constitutively activated with the generation of foci in unstimulated cells. Further, these cell lines exhibit near-maximal rates of proliferation even in the absence of catecholamine supplementation. They also demonstrate an enhanced ability for tumor generation in nude mice with a decreased period of latency compared with cells expressing the wild-type receptor. Thus, the alpha 1B-ADR gene can, when overexpressed and activated, function as an oncogene inducing neoplastic transformation. Mutational alteration of this receptor gene can result in the activation of this protooncogene, enhancing its oncogenic potential. These findings suggest that analogous spontaneously occurring mutations in this class of receptor proteins could play a key role in the induction or progression of neoplastic transformation and atherosclerosis.